Apparent Enhanced Solubility of Single-Wall Carbon Nanotubes in a Deuterated Acid Mixture. (30th April 2008) - Ramanathan, T.; Fisher, Frank T.; Ruoff, Rodney S.; Catherine Brinson, L.
Abstract : An apparent enhanced solubility of single-wall carbon nanotubes (SWNTs) in the deuterated form of the standard 3 : 1 sulfuric (H 2 SO 4 ) to nitric (HNO 3 ) acid mixture treatment is reported and attributed to the stronger interaction of deuterium bonds with the single-wall carbon nanotube surface. UV-Visible spectroscopy was used to characterize the apparent enhanced solubility of the SWNTs treated in deuterated forms of the acid mixture in comparison to the standard acid mix, while FTIR was used to analyze the nature of the functional groups generated on the SWNTs as a result of the different acid treatments. The apparent enhanced solubility reported here is consistent with the limited number of computational and experimental results published in the literature regarding the interaction of carbon nanotubes with deuterated solvents; however, a detailed understanding of the underlying mechanism responsible for this observation is currently lacking. The apparent increased solubility observed here could potentially be utilized in many applications where carbon nanotube dispersion is required.